Marital Property within the Marriage Law: A Debate on Legal Position and Actual Applications - Ibnu Elmi AS. Pelu; Ahmad Dakhoir (Al-Jami'ah Research Centre, 2021)
This paper presents a debate on the legal posistion of marital property and its application. It begins with examining the legal position of marital property and the application of the UUP and KHI for Muslims. It also pays attention to a discussion of whether the position of marital property needs to be declared in a marriage agreement or comes into effect automatically in every marriage. It ends with examining various actual applications in resolving a legal dispute over the marital property in the Indonesian Religious Courts. As qualitative research, this study adopts a socio-historical approach. Data were taken from such regulations on the marital property as the UUP and KHI, official documents released by the Supreme Court of the Republic of Indonesia. The data were also collected from books and reputable journals. Based on the socio-historical analysis, it could be concluded that the legal position of marital property distribution has been regulated in the UUP and KHI coming into force nationally. Under this legal framework, the property acquired during a marriage belongs to both spouses. In practice, however, the spousal rights to share the property ownership becomes broken in two situations, i.e., when the husband and wife agree to include the formulation of the distribution of marital property in their marriage agreement, and when one of them files a lawsuit for the marital property by either litigation or non-litigation. Decisions based on the qualitative contributions have turned out to be more dominant in the history of settling disputes over marital property in Indonesia.[Artikel ini membahas perdebatan posisi hukum dari harta bersama beserta penerapannya. Pembahasan diawali dari posisi hukum harta bersama dan penerapannya didalam UU Perkawinan dan Kompilasi Hukum Islam (KHI). Hal ini juga dibahas apakah perlu dicantumkan dalam perjanjian nikah atau otomatis menjadi bagian dari setiap pernikahan. Selain itu artikel ini juga membahas beberapa penerapan dalam penyelesaian kasus hukum harta bersama di Peradilan Agama. Artikel ini menggunakan pendekatan sosio-historis dan tidak hanya menggunakan rujukan dari buku serta jurnal ilmiah, tetapi juga dari dokumen resmi peraturan perundangan dalam UU Perkawinan, KHI serta Mahkamah Agung. Dalam tulisan ini disimpulkan bahwa harta bersama sudah mempunyai posisi legal dalam UU Perkawinan dan KHI serta diterapkan secara nasional. Dalam logika hukum ini, harta yang didapatkan selama pernikahan menjadi milik bersama. Dalam praktiknya, hak keduanya akan terbagi jika berada di dua kondisi, pertama ketika suami dan istri memasukkan formasi pembagian sendiri dalam perjanjian pernikahan dan kedua ketika salah satu dari pasangan tersebut mengajukan gugatan harta kekayaan baik lewat pengadilan atau tidak. Keputusan yang berdasarkan kontribusi kualitatif ternyata lebih dominan dalam sejarah penyelesaian perselisihan harta bersama di Indonesia.]